ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PERPUTARAN KARYAWAN DI PT. BANK MESTIKA DHARMA, TBK. ZAINUL ARIFIN MEDAN - Evania Tanady; Wily Julitawaty; Nur Subiantoro (JURNAL BISNIS KOLEGA, 2022)
Leadership style is the ability, strength, method, or method that is done by a leader to do something, take a decision, to build a good relationship between leader and employee. Leaders and employees can be integrated to create strategies to achieve company goals. The work environment is the location where tasks are completed, or where employees work in a company. The work environment can include the location, economic conditions, socio-cultural that may affect the company. Employee Turnover is a period when employees decide to quit their place of work or company and employee turnover does not always have a negative impact on the company. Employee turnover occurs when employees who stop working are employees who lack competence and ability to work at the company.The method used in this study is a survey approach, the type of research is quantitative descriptive and the nature of this research is explanatory research. The population in this study were all employees of PT. Bank Mestika Dharma, Tbk. Zainul Arifin Medan, amounting to 500 people with sampling using the Slovin formula were 222 people. Data collection method is done by distributing a list of statements, observations and study documentation. Variables are measured with a Likert scale. The model of data analysis used to answer hypotheses is multiple regression. The research results showed that the leadership style and work environment together had a positive influence on the employee turnover rate of PT. Bank Mestika Dharma, Tbk. Zainul Arifin Medan. Where the two variables affect the desire to work long-term employees, but in this study the two variables are not the main reason for employees to stop working. Partially, the work environment variable has a more dominant influence on the employee turnover of PT. Bank Mestika Dharma, Tbk. Zainul Arifin Medan instead of leadership style variables.Â Keywords : Leadership Style, Work Environment, Employee Turnover